IMPLEMENTASI PENDIDIKAN KEWIRAUSAHAAN USIA SEKOLAH DASAR MELALUI GLOBAL ENTREPRENEURSHIP WEEK (GEW) DI SD PEMBANGUNAN JAYA TANGERANG SELATAN - Syiddin, Najla Priniza; Yuliana, Rina; Taufik, M. (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to describe the implementation of entrepreneurship education through the Global Entrepreneurship Week (GEW) program at SD Pembangunan Jaya, South Tangerang. Using a qualitative descriptive approach, data were collected from the principal, teachers, and students through interviews, observations, and documentation. Data were analyzed through data collection, reduction, presentation, and conclusion drawing, with validity tests including credibility, transferability, dependability, and confirmability. The implementation began with thorough planning by teachers and the Teacher Working Group (KKG) at the start of the academic year. The program included entrepreneurship learning, business planning, capital acquisition, production, and product sales. The findings revealed that entrepreneurship education through GEW successfully fostered entrepreneurial values among students, such as creativity in business design, communication in product presentation and sales, and teamwork. The program not only enhanced students’ knowledge of entrepreneurship but also developed essential skills for becoming competitive entrepreneurs. Evaluation by teachers and the principal was conducted to improve future implementation.